2007
DOI: 10.1007/s11103-007-9160-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the imprinted Polycomb Group Fie1 gene in maize endosperm requires demethylation of the maternal allele

Abstract: Imprinting refers to the epigenetic regulation of gene expression that is dependent upon gene inheritance from the maternal or paternal parent. Previously, we have identified two maize homologs of the single Arabidopsis Polycomb Group gene FIE. Here, we report on the expression pattern of these genes in individual gametes before and after fertilization, and on the role of DNA methylation in determining the maternal expression of the Fie1 gene. We found that Fie1 is neither expressed in the sperm, egg cell nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 44 publications
4
51
0
1
Order By: Relevance
“…Ubiquitously expressed FIE2 and MEZ1 and endosperm-specific FIE1 are reported to be imprinted in maize, expressed only from the female alleles (Haun et al 2007;Hermon et al 2007), and it is striking that expression of FIE2 and MEZ1 is unaffected under conditions of MGE and PGE (as is almost certainly FIE1, although there is some intersample variation between 5 DAP 4n  2n endosperms following 25 and 30 PCR cycles). This similarity of expression levels is also unexpected in view of the presence of two extra sets of female alleles in MGE.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitously expressed FIE2 and MEZ1 and endosperm-specific FIE1 are reported to be imprinted in maize, expressed only from the female alleles (Haun et al 2007;Hermon et al 2007), and it is striking that expression of FIE2 and MEZ1 is unaffected under conditions of MGE and PGE (as is almost certainly FIE1, although there is some intersample variation between 5 DAP 4n  2n endosperms following 25 and 30 PCR cycles). This similarity of expression levels is also unexpected in view of the presence of two extra sets of female alleles in MGE.…”
Section: Resultsmentioning
confidence: 99%
“…Regions in the maize imprinted genes Mez1, ZmFie1, and ZmFie2 also display differential DNA methylation between the parental alleles in the imprinted tissue. For the ZmFie1 and ZmFie2 genes, transposon and repeat sequences, respectively, are present in the 59-proximal region but are not targeted for differential DNA methylation (Gutierrez-Marcos et al 2006;Hermon et al 2007). Additionally, Gutierrez-Marcos et al (2006) demonstrated imprinted expression and differential DNA methylation of ZmFie1-GUS and ZmFie2-GFP transcriptional fusions containing $4 kb of promoter and downstream sequence elements.…”
Section: G Enomic Imprinting Is An Epigenetic Phenomenonmentioning
confidence: 99%
“…During male gametogenesis, these genes were repressed in sperm cells by the action of MET1 (Jullien et al, 2006;Tiwari et al, 2008). During endosperm development, the inherited paternal allele remains silenced by MET1, whereas the inherited maternal alleles are transcriptionally active (Gutiérrez-Marcos et al, 2006;Hermon et al, 2007;Tiwari et al, 2008). It was therefore suggested that the differential expression between the two parental alleles is established by the status of DNA methylation that has been epigenetically inherited from the gametes (Huh et al, 2007).…”
Section: Genomic Imprinting and Early Seed Developmentmentioning
confidence: 99%